Morpho-Genetic Variability in F2 Progeny Cowpea Genotypes tolerant to bruchid (Callosobruchus maculatus) - amusa, oluwafemi D.; ogunkanmi, adebayo L.; Adetumbi, johnson A.; akinyosoye, solomon T.; ogundipe, oluwatoyin T. (Journal of Agricultural Sciences (Belgrade), 2019)
Callosobruchus maculatus Fab., is a major threat to cowpea production reducing the quality, quantity and market value of cowpea grains. A cheap and easy identification method would be a valuable a tool in identifying and breeding resistant genotypes in the vast cowpea germplasm. Hence, the purpose of the study was to identify and evaluate the genetics of cowpea traits between resistant and susceptible plant genotypes to C. maculatus. Contrasting qualitative and quantitative traits in C. maculatus resistant and susceptible parents were evaluated in 72 F2 progeny cowpea plants. Heritability, segregation and association of investigated traits with the C. maculatus resistant performance of the F2 cowpea genotypes were evaluated to determine closely related traits with C. maculatus resistant. Results from the study showed high heritability for all cowpea quantitative traits except leaf petiole length. Both Mendelian and non-Mendelian inheritance was observed among qualitative traits. However, association evaluation between cowpea traits and mean bruchid development period, percentage adult emergence and oviposition preference were weak (r < 0.5) and not significant (p < 0.05). This indicates that C. maculatus resistance in cowpea may be attributed to factors other than morphological variations.
Keywords: morphology; resistant; variability; susceptibility; Cowpeas; Callosobruchus